Self-medication among university students during the COVID-19 pandemic: a comparative analysis of different faculties - Maria Letícia Carnielli Tebet; Ricardo Pasquini Neto; Ariele Barreto Haagsma; Gracinda Maria D’Almeida e Oliveira; Marcia Olandoski (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Self-medication is a widespread public health concern. University students are likely to be more prone to it since self-medication rates increase with educational level. Studies have shown that self-medication rates vary among academics belonging to different faculties, and medical students have the highest self-medication rates. However, it is unknown whether this holds in a vulnerable situation, such as the COVID-19 pandemic. It is also unknown whether differences in technical knowledge of drugs influence self-medication rates among students. Thus, this study analyzes and compares prophylactic self-medication among graduate students of different faculties in the context of the COVID-19 pandemic. This cross-sectional observational study was conducted at a private university in southern Brazil. Students from the medicine, law, life sciences, and fine arts faculties were surveyed, and their responses were compared using a chi-square test. Among 396 respondents, 29.5% reported using preventive medication for COVID-19, and medical students were the least likely to do so. The self-medication rate was 13.6% among respondents, and self-medication did not differ significantly between students of different faculties. Of the students who self-medicated 63% reported having studied the medication before using them. Furthermore, the media did not induce drug use among 81.8% respondents. These results show that medical students used fewer preventive medications during the pandemic and refute the assertion that self-medication rates are higher among medical students. They also show that self-medication rates during the pandemic were significantly lower than those before the pandemic. These revelations show a new aspect of self-medication.